The logical foundations of social theory - Mueller, Gert H. (Gert Harald), 1922- (University Press of America, 2014)
The Logical Foundations of Social Theory describes Gert Mueller's argument that physical, biological, social, moral, and cultural reality form an asymmetrical hierarchy of founding and controlling relationships that condition social reality rather than mechanically determining it. This book analyzes social stratification, the moral order, and culture systems.